Population Traits and a Female Perspective for Aglae and Exaerete, Tropical Bee Parasites (Hymenoptera, Apinae: Euglossini) - David W. Roubik (Psyche: A Journal of Entomology)
Size variation of both males and females leads to taxonomic confusion regarding wholly parasitic euglossines. The six most widespread species, Exaerete frontalis, E. smaragdina, E. dentata, E. trochanterica, E. lepeletieri, and Aglae caerulea, ranged from 12.5 to 28 mm in length (n = 522; 50 females; 472 males), and within species, some were 40-80% larger than others. The size of E. lepeletieri matches E. smaragdina and E. dentata, but not E. frontalis, which it was said to resemble. Female E. lepeletieri, here described from Amazonian Ecuador, has a range shown to also include French Guiana and Suriname. Female Aglae and Exaerete were larger than males. Statistically, female Exaerete tended toward larger individuals more than did males. Each species should parasitize Eulaema and Eufriesea that have comparable size and provisions; thus multiple hosts may cause parasite size variation. Unknown factors may promote host resource partitioning between sympatric parasites, which include up to six in Yasuní Biosphere Reserve, Ecuador, the richest known euglossine community. Scutellum and metafemur punctation, sculpture and the frontal knob of both sexes, and male mesotibial tuft and metafemur permit easy identification of the six common species and E. azteca. Existence of E. kimseyae in Panama is questionable, while E. dentata there is certainly rare. The female tibial scoop, a structure in both Aglae and Exaerete, with a proposed function in material transport, is discussed. No new phylogenetic interpretation is presented.